2014
DOI: 10.1530/rep-13-0594
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs in spermatogenesis: insights from recent high-throughput transcriptome studies

Abstract: Spermatogenesis is a complex developmental process in which undifferentiated spermatogonia are differentiated into spermatocytes and spermatids through two rounds of meiotic division and finally giving rise to mature spermatozoa (sperm). These processes involve many testis-or male germ cell-specific gene products that undergo strict developmental regulations. As a result, identifying critical, regulatory genes controlling spermatogenesis provide the clues not only to the regulatory mechanism of spermatogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 69 publications
0
52
0
Order By: Relevance
“…The second most abundant miRNA observed in the present study, miR-365-2 , is known to have BCL2 as one of its targets33, and the suppression of BCL2 is essential for the progression of a fertilized oocyte into the cleavage stage; therefore sperm-derived factors are thought to be essential for the development of preimplantation embryos34. Although a role of long non-coding RNA (lncRNA) on spermatogenesis has been reported35, further studies are essential in bovine to better understand the roles of ncRNAs on spermatozoa fertility.…”
Section: Discussionmentioning
confidence: 69%
“…The second most abundant miRNA observed in the present study, miR-365-2 , is known to have BCL2 as one of its targets33, and the suppression of BCL2 is essential for the progression of a fertilized oocyte into the cleavage stage; therefore sperm-derived factors are thought to be essential for the development of preimplantation embryos34. Although a role of long non-coding RNA (lncRNA) on spermatogenesis has been reported35, further studies are essential in bovine to better understand the roles of ncRNAs on spermatozoa fertility.…”
Section: Discussionmentioning
confidence: 69%
“…LncRNAs can regulate the expression of coding genes by epigenetic modification or induce recruitment to specific target sites, such as for DNA methylation and histone modification [2830]. Accumulating evidence has shown that irregularities of lncRNAs in sperm could act as markers and potential therapeutic targets of male infertility [31]. The dynamic change of lncRNA expression during mouse testis postnatal development also indicated that lncRNAs might play crucial roles in mammalian testis development and spermatogenesis [32].…”
Section: Introductionmentioning
confidence: 99%
“…Spermatogonia differentiate into spermatocytes and spermatids during two meiotic divisions, which leads to the production of mature sperm (3). Defects at any stage of this process may lead to infertility.…”
Section: Introductionmentioning
confidence: 99%